MESQUITA, Vianney. "Franciscos Moradores do Céu” - Melo Lima, Myrson (Kairós: Revista Acadêmica da Prainha, 2021)
MESQUITA, Vianney. "Franciscos Moradores do Céu”. Palmácia: Arcádia Nova Palmaciana, 2018.